Strutural and optical approach of CdS@ZnS core-shell system - Raubach, Cristiane W.; de Santana, Yuri V. B.; Ferrer, Mateus M.; Longo, Valeria M. [UNESP]; Varela, José Arana [UNESP]; Avansi, Waldir [UNESP]; Buzolin, Prescila G. C. [UNESP]; Sambrano, Julio R. [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2012)
An intense red-green photoluminescence (PL) emission was observed, at room temperature, in a CdS@ZnS core-shell system. The PL intensity emission of CdS@ZnS core-shell was strongly superior from that observed in individual CdS and ZnS nanoparticles. In this sense, we reported a comprehensive experimental and theoretical study of the optical behavior of CdS and ZnS nanoparticles (NPs), and CdS@ZnS core-shell system in the light the structural order-disorder conception. We also propose a model were the core and shell interface leads to favorable condition that triggers PL emission in CdS@ZnS core-shell. (C) 2012 Elsevier B. V. All rights reserved.